Ion exchange and solvent extraction : supramolecular aspects of solvent extraction - Moyer, Bruce A. (Ion exchange and solvent extraction series, 2014)
Over the past several decades, the theme of supramolecular chemistry (SC) has permeated nearly all aspects of chemical endeavor. Not surprisingly, it has also pervaded the field of solvent extraction (SX), inspiring the framework for this volume of Ion Exchange and Solvent Extraction. In addition, tools for studying aggregation have grown increasingly sophisticated, leading to a greater understanding of what we now recognize as SC phenomena in SX. Volume 21, Supramolecular Aspects of Solvent Extraction identifies how supramolecular behavior occurs and is studied in the context.